[OP.8B.04] GENDER DIFFERENCES IN THE IMPACT OF DYSFUNCTIONAL COPING IN A HYPERTENSIVE POPULATION. (September 2016) - Bruno, R.; Ghiadoni, L.; Cervia, S.; Biancheri, R.; Mauri, M.; Taddei, S.; Palagini, L.
Abstract : Objective: Chronic stress and coping strategies might influence cardiovascular health in a gender-dependent manner. Aim of this study is to investigate their impact on blood pressure control in men and women attending for the first time a visit in a Hypertension Outpatient Clinic. Design and method: Data from 330 patients were analyzed (males 51%, mean age 57 ± 13 years, antihypertensive treatment 84%, previous CV events 9%, diabetes 7%, obesity 24%, smoking 13%, hypercholesterolemia 67%). Office blood pressure (BP) was measured, and medical history collected. Perceived Stress Scale (PSS), Brief-COPE, Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), and State-Trait Anxiety Inventory (STAY-Y2) were administered. Results: Women were older and less obese, and showed lower office BP than men. Sleep quality was similar among men and women, while women showed higher STAI-Y2 and BDI values. Despite similar perceived stress, women showed higher emotion-focused and dysfunctional coping. In the overall population, univariate regression analysis showed that systolic BP was directly correlated with triglycerides and dysfunctional coping and inversely correlated with HDL. These correlations were confirmed in men, but not in women. In men, a multiple regression model, considering age, body mass index, diabetes, HDL, Triglycerides, number of antihypertensive drugs, STAI-Y2, BDI and dysfunctional coping, as independent variables, demonstrated that only diabetes (beta 12.9, p = 0.04), number of antihypertensive drugs (beta -3.39, p = 0.05) and dysfunctional coping (beta 0.91, p = 0.03) were significantly associated with systolic BP. The model explained 23% of the variance of systolic BP, while dysfunctional coping 6%. Conversely in women only diabetes (p = 0.049) was positively associated with systolic BP. Conclusions: Maladaptive coping strategies seems to translate into unfavorable cardiovascular outcome in men but not in women.